Guided by Augmented Reality: The Results of Multiple Experiments Conducted to Enhance the Visitor Experience at a Culturally Historic Site - Damian Schofield; Paul Lear; Daniel Hufnal; Theodore Johnson; Sarah Colletta; Pranay Chapagain (Science and Technology - Recent Updates and Future Prospects Vol. 2, 2024)
In recent years, museums and historic sites have expanded their reach beyond traditional audiences by embracing innovative digital display technologies. Among these technologies, virtual, mixed, and augmented reality (AR) have gained prominence in society. These “virtual history” exhibits aim to bring historical narratives to life, allowing visitors to engage with the past in novel ways. However, the successful implementation of AR in cultural heritage contexts requires careful consideration of usability factors and alignment with media creators’ intended meanings. Our research investigates the use of various AR technologies within cultural heritage applications. Specifically, we conducted multiple experiments at a historic fort in upstate New York, evaluating the impact of digital display technology on-site visitors. By analyzing user experiences, we aimed to understand how AR enhances cultural exploration and engagement. Key areas of focus include: Usability Factors: We examined how visitors interacted with AR applications, considering ease of use, navigation, and overall satisfaction. Human-Computer Interaction: Understanding how users engage with AR interfaces and interpret historical content. Evaluation: Assessing the effectiveness of AR displays in conveying cultural heritage information. Our findings contribute to the ongoing discourse on leveraging AR for cultural preservation and education. By bridging the gap between physical artifacts and virtual imagery, AR can enrich visitors’ understanding of historical contexts. As museums and heritage sites continue to embrace digital technologies, thoughtful design and evaluation are crucial for creating meaningful and immersive experiences. In summary, this research sheds light on the potential of AR to augment cultural exploration, enhance visitor engagement, and breathe new life into historical narratives. By blending technology and heritage, we pave the way for a more dynamic and accessible appreciation of our shared past.